(untitled) (Research, Society and Development, 2022)
Introduction: Squamous cell carcinoma represents the most frequent malignant neoplasm in the oral cavity, and its incidence is more recurrent in patients who smoke and/or drink alcohol, being even more evident when they are male and of advanced age. In addition, histopathological analysis is essential for the detection of oral malignancy. Methodology: The following research question was developed: What are the main histopathological characteristics for the diagnosis of squamous cell carcinomas? For this, the electronic database: U. S. National Library of Medicine (PubMed) was used to search and identify studies that answered the guiding question of this integrative literature review. The database was searched for studies carried out between January 1990 and April 2022. Two descriptors were used to compose the search key, the following (MeSH): “Squamous cell carcinoma”; “Histopathological”; "Dentistry". Then, the researchers selected the works with analysis in the title and abstract, based on the eligibility criteria. Eligibility criteria were as follows: articles published in English, Portuguese and Spanish; publications between January 2000 and April 2022; human research; articles that fit the theme. The advanced form system was also used to search and select articles using the Boolean “AND” connector. Then, articles that met the eligibility criteria were identified and included in the review. Results and discussion: Based on this search strategy, a total of 521 works were found in full; of these, 4 articles were duplicated in the search strategies, thus totaling 10 selected. The histological characteristics varied in each case, and some tumor infiltrations, atypical mitotic proliferations and subcutaneous infiltrations of lymphatic cells could be found. Final considerations: The histopathological examination is an important tool in the prior identification of SCC, helping in the clinical detection before the development of the neoplasm. Allied to this, it is necessary for the Dental Surgeon to pay close attention to potentially malignant lesions, such as leukoplakia and erythroplakia, since most oral cancers are diagnosed late, which impairs therapy and facilitates the spread of tumor cells.